2020
DOI: 10.3390/ijms21176177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium and Halide Ions on the Gramicidin A Molecular State and Antimicrobial Activity

Abstract: Gramicidin A (gA) forms several convertible conformations in different environments. In this study, we investigated the effect of calcium halides on the molecular state and antimicrobial activity of gramicidin A. The molecular state of gramicidin A is highly affected by the concentration of calcium salt and the type of halide anion. Gramicidin A can exist in two states that can be characterized by circular dichroism (CD), mass, nuclear magnetic resonance (NMR) and fluorescence spectroscopy. In State 1, the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Both the hydroxyl free radical formation and dysregulation of the NAD + /NADH mechanism have been linked with the antimicrobial activity of gramicidin A [ 18 ]. Also, the antimicrobial activity of gramicidin A is highly associated with the conformation of gramicidin A [ 19 , 20 , 21 ]. Several studies have demonstrated that gramicidin A, only in a channel form, is able to proceed with its antimicrobial activity [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both the hydroxyl free radical formation and dysregulation of the NAD + /NADH mechanism have been linked with the antimicrobial activity of gramicidin A [ 18 ]. Also, the antimicrobial activity of gramicidin A is highly associated with the conformation of gramicidin A [ 19 , 20 , 21 ]. Several studies have demonstrated that gramicidin A, only in a channel form, is able to proceed with its antimicrobial activity [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the antimicrobial activity of gramicidin A is highly associated with the conformation of gramicidin A [ 19 , 20 , 21 ]. Several studies have demonstrated that gramicidin A, only in a channel form, is able to proceed with its antimicrobial activity [ 19 , 20 , 21 ]. Ca 2+ ions have been found to block the translocation of alkali cations of gA across membrane lipids and convert gA double helical dimers into helical monomers [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations